EFFECT OF SELF-EFFICACY AND FAMILY ENVIRONMENT ON BUSINESS INTENSION - Tri Wahyu yeti Akpiya (Fakultas Ekonomi Universitas Negeri Jakarta, 2018)
Self-efficacy and family support are some of the factors that foster student entrepreneurial intentions. With the high self-efficacy and support from the family environment, students are expected to have entrepreneurial intentions after graduating from college. The formulation of the problem of this research is about the self-efficacy (X1) and family environment (X2) on entrepreneurship intentions (Y) in students of economic education at STKIP PGRI Tulungagung. The data collection method uses a questionnaire. This method is used to obtain data on self-efficacy (X1), family environment (X2) and entrepreneurial intentions (Y). The instrument used consists of questions with available answers consisting of 5 (five) choices with a score = answer strongly agree score 5, answer agree score 4, doubt answer score 3, answer disagree score 2, answer strongly disagree score 1, the sum of each variable is 20 questions so that the lowest value is 20 and the highest value is 100. To find out the relationship between variables X and Y use the evaluation formula when the product is rough. From the analysis of the data, it was proven that a large t-test on self-efficacy (X1) was obtained t count (6,066)> t table (1,987) and a significance value of 0,000 <0.05 which was significant. So arithmetic> t table can be concluded that the self-efficacy variable has a significant effect on entrepreneurial intentions which means that Ho is rejected and Ha is accepted. While the test on the family environment (X2) shows a value (5,010)> t table (1,987) and a significance value of 0,000 <0.05 means significant. So arithmetic> t table can be summed up as a variable family environment rate significantly towards entrepreneurial intention.